Method for improving piezoelectric property of lithium niobate ceramic through Na doping
By introducing Na elements into lithium niobate ceramics and adopting specific process steps, the problem of insufficient piezoelectric properties of pure lithium niobate ceramics is solved, and its piezoelectric constant and ferroelectric properties are significantly improved, which is suitable for high-temperature piezoelectric sensors.
Patent Information
- Application Number
- CN202411656397.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
AI Technical Summary
Pure lithium niobate ceramics have weaker piezoelectric properties than their single crystal materials, making it difficult to meet the needs of high-temperature piezoelectric sensors.
By introducing Na elements into lithium niobate ceramics, the microstructure and electrical properties of the ceramics are optimized by introducing Na elements into lithium niobate ceramics. Specific process steps include mixing, reaction, hydrogen passing, ball milling, sintering, oxygenation, slice and polarization.
The piezoelectric constant of lithium niobate ceramics has been significantly improved, from 25 pC/N to above 36 pC/N, enhancing its ferroelectric properties and piezoelectric effects, and can effectively replace pure lithium niobate ceramics in the field of high-temperature piezoelectric.
Smart Images

Figure CN119504262A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of piezoelectric ceramic preparation, and in particular to a method for improving the piezoelectric properties of lithium niobate ceramics by Na doping. Background Art
[0002] Lithium niobate material has the advantages of high Curie temperature, large piezoelectric constant, low dielectric loss, large electromechanical coupling coefficient, and good temperature stability. It can be used to prepare high-temperature piezoelectric sensors, surface acoustic wave filters and other devices. Currently, most high-temperature piezoelectric sensors used above 600°C use lithium niobate single crystals, but the single crystals have poor thermal shock and mechanical impact resistance, and are prone to fracture failure under long-term mechanical loads. In addition, due to the presence of isotropic eutectic points in the lithium niobate single crystal growth system Li2O-Nb2O5, it is difficult to grow lithium niobate single crystals that meet the stoichiometric ratio. In addition, the growth cycle of lithium niobate single crystals is long, the processing performance is poor, and the cost is high. Compared with lithium niobate single crystals, lithium niobate ceramics have the advantages of good processing performance and short preparation cycle. They have more advantages than single crystals in terms of processability and cost, and the chemical composition can strictly meet the stoichiometric ratio. It is one of the best candidate materials to replace lithium niobate single crystals in the field of high-temperature piezoelectric sensing. However, the piezoelectric properties of pure lithium niobate ceramics are weaker than those of their single crystal materials, so technical methods are needed to improve their piezoelectric properties. Summary of the invention
[0003] In view of the above disadvantages, the present invention proposes a method for improving the piezoelectric properties of lithium niobate ceramics by Na doping, comprising the following steps: Mixing S1: Li2CO3, Na2CO3, and Nb2O5 are weighed in a molar ratio of 0.985-0.995: 0.005-0.015: 1 to obtain a mixed powder, and then 5%-8% of anhydrous ethanol by weight of the mixed powder is added, and then ball milling is performed for 18-22 hours, and then taken out and dried in an oven to obtain a dry powder; Reaction S2: Place the above dried powder into a vacuum atmosphere furnace, evacuate the vacuum and raise the temperature to not less than 800°C, keep the temperature, and control the pressure in the furnace to 1.0-1.5×10 -3 Pa, the temperature is raised to not less than 950°C, and the temperature is kept for 2 to 4 hours. The reaction product is Na-doped lithium niobate powder; wherein the composition of the Na-doped lithium niobate powder is: Li 0.985-0.995 Na 0.005-0.015 NbO3; Hydrogen supply S3: After the insulation is completed, hydrogen is introduced into the vacuum atmosphere furnace to maintain the pressure in the furnace at 1.0~1.2×10 5 Pa, keep the temperature in the furnace not less than 950°C, keep it warm for 5 to 6 hours, and obtain Na-doped lithium niobate powder rich in oxygen vacancy defects; wherein the composition of the Na-doped lithium niobate powder is: Li 0.985-0.995 Na0.005-0.015 NbO 3-x , x is the number of oxygen vacancy defects in a single unit cell; Ball milling S4: ball milling the Na-doped lithium niobate powder to make its average particle size less than 3 μm; Sintering S5: The ball-milled Na-doped lithium niobate powder is sintered at high temperature. The sintering process conditions are: vacuuming the furnace until the pressure inside is no higher than 10 -3 Pa, the die stamping pressure is 50-80MPa, the heating rate is 80-100℃ / min, the temperature is raised from room temperature to not less than 950℃, kept at this temperature for 15-30min, cooled to not more than 600℃ at a rate of 15-25℃ / min, and then furnace cooled to obtain Na-doped lithium niobate ceramics; the composition of the Na-doped lithium niobate ceramics is: Li 0.985-0.995 Na 0.005-0.015 NbO 3-x ; Oxygenation S6; Slicing S7: cutting the above-mentioned Na-doped lithium niobate ceramic sheet without oxygen vacancy defects into blocks; Polarization S8: Place the above block into a high-voltage polarization device for polarization to obtain a polarized Na-doped lithium niobate ceramic sheet. BRIEF DESCRIPTION OF THE DRAWINGS
[0004] Figure 1 The Li of the ceramic sheet formed in Example 1 0.985 Na 0.015 XRD spectrum of NbO3 ceramics. As can be seen from the figure, the lithium niobate ceramics doped with Na are a single lithium niobate phase, without the appearance of a second phase, indicating that the lithium niobate phase does not change after a certain amount of Na is doped, and the Na element enters the lithium niobate lattice in the form of replacement atoms.
[0005] Figure 2 For Li 0.985 Na 0.015 SEM photos of the cross section of NbO3 ceramics and elemental surface scanning photos. This figure shows that the elements in the lithium niobate ceramics doped with Na are evenly distributed, and the Na element is evenly distributed in the ceramics.
[0006] Figure 3 For Li 0.985 Na 0.015 Hysteresis loop of NbO3 ceramics. As can be seen from the figure, the residual polarization strength of lithium niobate ceramics doped with Na is 1.35μC / cm 2 This indicates that the ceramic has good ferroelectric properties and can have a good piezoelectric effect after medium and high voltage polarization at an electric field strength of 15kv / mm. DETAILED DESCRIPTION
[0007] The method for improving the piezoelectric properties of lithium niobate ceramics by Na doping proposed in the present invention comprises the following steps: Mixing S1: Li2CO3, Na2CO3, and Nb2O5 are weighed in a molar ratio of 0.985-0.995: 0.005-0.015:1 to obtain a mixed powder, which is put into a ball mill, and then 5%-8% of anhydrous ethanol by weight of the mixed powder is added, and then zirconium oxide grinding balls are added for 18-22 hours, and then taken out and dried in an oven to obtain a dry powder; Reaction S2: The above dry powder was placed in a high-purity alumina boat and placed in a vacuum atmosphere furnace. The temperature was raised to not less than 800°C at a heating rate of 10°C / min and kept at this temperature for 2 to 4 hours. The pressure in the furnace was controlled to be 1.0 to 1.5×10 -3 Pa, and obtain Na-doped lithium niobate powder; wherein the composition of the Na-doped lithium niobate powder is: Li 0.985-0.995 Na 0.005-0.015 NbO3; Hydrogen supply S3: After the insulation is completed, hydrogen is introduced into the vacuum atmosphere furnace to maintain the pressure in the pressure furnace at 1.0~1.2×10 5 Pa, keep the temperature in the furnace not less than 950°C, keep it warm for 5 to 6 hours, and obtain Na-doped lithium niobate powder rich in oxygen vacancy defects; wherein the composition of the Na-doped lithium niobate powder is: Li 0.985-0.995 Na 0.005-0.015 NbO 3-x , x is the number of oxygen vacancy defects in a single unit cell; Ball milling S4: putting the Na-doped lithium niobate powder into a ball milling jar for ball milling to make its average particle size less than 3 μm; Sintering S5: The ball-milled Na-doped lithium niobate powder is loaded into a graphite mold and then sintered at high temperature in a spark plasma sintering furnace. The sintering process conditions are: evacuate the air to not less than 10 -3 Pa, the die stamping pressure is 50-80MPa, the heating rate is 80-100℃ / min, the temperature is raised from room temperature to not less than 950℃, kept at this temperature for 15-30min, cooled to not more than 600℃ at a rate of 15-25℃ / min, and then furnace cooled to obtain Na-doped lithium niobate ceramics; the composition of the Na-doped lithium niobate ceramics is: Li 0.985- 0.995 Na 0.005-0.015 NbO 3-x ; Oxygenation S6; Slicing S7: Cut the above-mentioned oxygen-vacancy-free Na-doped lithium niobate ceramic sheet into blocks; use a diamond wire cutting machine to cut the above-obtained Na-doped lithium niobate ceramic into regular blocks of 5 mm×5 mm×0.5 mm, polish the upper and lower end faces of 5 mm×5 mm, coat them with silver paste, put them in a muffle furnace, heat them to 500°C and keep them warm for 10 minutes, and then cool them to room temperature at a cooling rate of 5°C / min to obtain Na-doped lithium niobate ceramic sheets coated with electrodes.
[0008] Polarization S8: Place the block in a high-voltage polarization device for polarization to obtain a polarized Na-doped lithium niobate ceramic sheet. Place the Na-doped lithium niobate ceramic sheet in a high-voltage polarization device and immerse it in methyl silicone oil, slowly heat it to 100°C, then apply a 15kv / mm high-voltage DC electric field at both ends of the electrode, keep it for 2 hours, and then cool it to room temperature to obtain a polarized Na-doped lithium niobate ceramic sheet.
[0009] In this scheme, the introduction of replacement Na atoms in the lithium niobate piezoelectric ceramic lattice is a way to dope and modify pure lithium niobate ceramics, and the piezoelectric properties are improved by doping. The present invention partially replaces Li atoms in the lithium niobate lattice with Na atoms, thereby achieving the purpose of improving the piezoelectric properties of lithium niobate ceramics. Compared with undoped pure lithium niobate, the level of piezoelectric constant is increased from 25 pC / N to more than 36 pC / N. And the replacement of Na atoms is first reacted in the powder mixing state, and after the replacement is completed, hydrogen is passed to prepare oxygen vacancy defects. The embodiment shows that the incorporation of Na atoms can significantly improve the piezoelectric properties compared with ceramics without Na doping.
[0010] In the present invention, the formation of lithium niobate and the sodium replacement are carried out simultaneously in the reaction step, and the chemical reactions that occur include:
[0011] yLi2CO3+(1-y) Na2CO3+Nb2O5→2Li y Na 1-y NbO3+ CO2↑ The Li generated by the above reaction y Na 1-y In high temperature and hydrogen atmosphere, some oxygen atoms of NbO3 are taken away to form Li y Na 1-y NbO 3-x , where x and y represent the number of oxygen vacancies and the number of Li atoms in a single unit cell. Only the chemical reaction principle is listed here, and the molar ratio is well known to those skilled in the art.
[0012] Since the reaction is carried out at high temperature, the reaction rate is fast. After the reaction, all Na atoms replace some Li atoms to form doped lithium niobate. In order to ensure that the material reaction temperature meets the theoretical temperature, the actual temperature is set slightly higher than the theoretical temperature, but this high temperature does not lead to the generation of impurities, such as Figure 1 , 2 It shows that no second phase is generated after the reaction.
[0013] Furthermore, the S6 oxygenation process is as follows: placing the Na-doped lithium niobate ceramic into an atmosphere heat treatment furnace, introducing oxygen, and maintaining the pressure in the furnace at not less than 1.05×10 5 Pa, heat up to not less than 850°C at a heating rate of 6 to 10°C / min, keep warm for 25 to 30 hours, and then cool to room temperature at a cooling rate of not more than 5°C / min to obtain Na-doped lithium niobate ceramics without oxygen vacancy defects. The creation of oxygen vacancy defects in Na-doped lithium niobate powder enables the powder to be densified at a sintering temperature of not more than 1000°C during sintering, which can avoid the loss of lithium. On the contrary, if the powder has no oxygen vacancy defects, the Na-doped lithium niobate powder cannot be highly densified at a sintering temperature below 1000°C. Therefore, in the S3 step of this scheme, oxygen vacancy defects are created by introducing hydrogen to improve the sintering performance of the powder, making adequate preparations for the high densification step (sintering) of the powder.
[0014] Furthermore, in the step S1 of mixing, the molar ratio of Li2CO3, Na2CO3, and Nb2O5 is 0.985: 0.015: 1, and the composition of the prepared Na-doped lithium niobate ceramic is: Li 0.985 Na 0.015 NbO 3-x .
[0015] Furthermore, in the step S1 of mixing, the molar ratio of Li2CO3, Na2CO3, and Nb2O5 is 0.995: 0.005: 1, and the composition of the prepared Na-doped lithium niobate ceramic is: Li 0.995 Na 0.005 NbO 3-x .
[0016] Furthermore, in the step S1 of mixing, the molar ratio of Li2CO3, Na2CO3, and Nb2O5 is 0.99: 0.01:1, and the composition of the prepared Na-doped lithium niobate ceramic is: Li 0.99 Na 0.01 NbO 3-x .
[0017] Furthermore, in the polarization step, the polarization condition is to apply a high-voltage direct current electric field of not less than 15 kv / mm at both ends of the electrode, maintain it for 1.5 to 2 hours, and then cool it to room temperature to obtain a polarized Na-doped lithium niobate ceramic. Further, in the polarization step, before applying a high-voltage direct current electric field at both ends of the electrode, the above-mentioned Na-doped lithium niobate ceramic sheet is placed in a high-voltage polarization device, immersed in methyl silicone oil, and slowly heated to 100°C.
[0018] The present invention also proposes a Na-doped lithium niobate ceramic, the piezoelectric constant of which after polarization is 36.0-39.1 pC / N, which can completely replace pure lithium niobate ceramics as high-temperature piezoelectric ceramics. At the same time, the piezoelectric constant of the doped lithium niobate ceramic is 36.0-39.1 pC / N, which is at least 42.86% higher than that of pure lithium niobate ceramics (25.2 pC / N), and the piezoelectric performance is significantly improved.
[0019] Furthermore, the Curie temperature of the Na-doped lithium niobate ceramic is not less than 1190° C., the relative density is not less than 99.3%, and the piezoelectric constant is 36.0-39.1 pC / N. Example 1
[0020] A method for preparing sodium-doped lithium niobate piezoelectric ceramics comprises the following steps: Mixing S1: Li2CO3, Na2CO3, and Nb2O5 were weighed in a molar ratio of 0.985: 0.015:1 to obtain a mixed powder, which was put into a ball mill, and then 8% of anhydrous ethanol by weight of the mixed powder was added, and then zirconium oxide grinding balls were added for 18 hours, and then taken out and dried in an oven to obtain a dry powder; Reaction S2: The above dry powder was placed in a high-purity alumina boat and placed in a vacuum atmosphere furnace. The temperature was raised to 800°C at a heating rate of 10°C / min and kept at this temperature for 2 h. The pressure in the furnace was controlled to be 1.2×10 -3 Pa, and heated to not less than 950°C at a heating rate of 20°C / min, and kept at this temperature for 2.5 hours to obtain Na-doped lithium niobate powder; wherein the composition of the Na-doped lithium niobate powder is: Li 0.985 Na 0.015 NbO3; Hydrogen flow S3: After the insulation is completed, hydrogen is introduced into the vacuum atmosphere furnace to maintain the pressure in the pressure furnace at 1.0×10 5 Pa, maintaining the furnace temperature at 950°C for 5 hours, and obtaining Na-doped lithium niobate powder rich in oxygen vacancy defects; wherein the composition of the Na-doped lithium niobate powder is: Li 0.985 Na 0.015 NbO 3-x , x is the number of oxygen vacancy defects in a single unit cell; Ball milling S4: putting the Na-doped lithium niobate powder into a ball milling jar for ball milling, and the average particle size after ball milling is less than 3 μm; Sintering S5: The ball-milled Na-doped lithium niobate powder is loaded into a graphite mold and then sintered at high temperature in a spark plasma sintering furnace. The sintering process conditions are: evacuate to 10 -3 Pa, the die stamping pressure is 50MPa, the heating rate is 100℃ / min, the temperature is raised from room temperature to 950℃, kept at this temperature for 30min, cooled to 600℃ at 25℃ / min, and then furnace cooled to obtain Na-doped lithium niobate ceramics; the composition of the Na-doped lithium niobate ceramics is: Li 0.985 Na 0.015 NbO 3-x ; Oxygen-enhanced S6: Place the Na-doped lithium niobate ceramic into an atmosphere heat treatment furnace, introduce oxygen, and keep the pressure in the furnace at 1.05×10 5 Pa, heated to 850°C at a heating rate of 10°C / min, kept at that temperature for 30h, and then cooled to room temperature at a cooling rate of 5°C / min to obtain Na-doped lithium niobate ceramics without oxygen vacancy defects; Slicing S7: Cut the above-mentioned oxygen-free lithium niobate ceramic sheet into blocks; use a diamond wire cutting machine to cut the above-obtained Na-doped lithium niobate ceramic into regular blocks of 5 mm×5 mm×0.5 mm, polish the upper and lower end faces of 5 mm×5 mm, coat them with silver paste, put them in a muffle furnace, heat them to 500°C and keep them warm for 10 minutes, then cool them to room temperature at a cooling rate of 5°C / min to obtain Na-doped lithium niobate ceramic sheets coated with electrodes.
[0021] Polarization S8: Place the above block into a high-voltage polarization device for polarization to obtain a polarized Na-doped lithium niobate ceramic sheet. Example 2
[0022] The other steps are the same as those in Example 1, and the process parameters are slightly adjusted. The difference is: Mixing S1: Li2CO3, Na2CO3, and Nb2O5 are weighed in a molar ratio of 0.995: 0.005: 1 to obtain a mixed powder; Reaction S2: Keep warm for 4 hours to obtain Na-doped lithium niobate powder; wherein the composition of the Na-doped lithium niobate powder is: Li 0.995 Na 0.005 NbO3; Hydrogen S3: Keep warm for 6 hours to obtain Na-doped lithium niobate powder rich in oxygen vacancy defects; wherein the composition of the Na-doped lithium niobate powder is: Li 0.995 Na 0.005 NbO 3-x , x is the number of oxygen vacancy defects in a single unit cell; Ball milling S4: Same as in Example 1.
[0023] Sintering S5: Same as Example 1.
[0024] Oxygenation S6: Same as in Example 1.
[0025] Slice S7: Obtain a Na-doped lithium niobate ceramic slice coated with an electrode.
[0026] Polarization S8: Same as Example 1. Example 3
[0027] The other steps are the same as those in Example 1, and the process parameters are slightly adjusted. The difference is: Mixing S1: Li2CO3, Na2CO3, and Nb2O5 were weighed in a molar ratio of 0.99: 0.01:1; Reaction S2: Keep warm for 3 hours to obtain Na-doped lithium niobate powder; wherein the composition of the Na-doped lithium niobate powder is: Li 0.99 Na 0.01 NbO3; Hydrogen is passed through S3: the temperature is kept for 5.5 hours to obtain Na-doped lithium niobate powder rich in oxygen vacancy defects; wherein the composition of the Na-doped lithium niobate powder is: Li 0.99 Na 0.01 NbO 3-x , x is the number of oxygen vacancy defects in a single unit cell; Ball milling S4: Same as in Example 1.
[0028] Sintering S5: Same as Example 1.
[0029] Oxygenation S6: Same as Example 1.
[0030] Slice S7: Obtain a Na-doped lithium niobate ceramic slice coated with an electrode.
[0031] Polarization S8: Same as Example 1.
[0032] The polarized ceramic sheets of the three embodiments were tested respectively, and the following table was obtained.
[0033] Piezoelectric constant Curie temperature Relative density Example 1 39.1 pC / N 1194℃ 99.28% Example 2 37.8 pC / N 1196℃ 99.39% Example 3 38.6pC / N 1195℃ 99.33% The table above shows that in the three embodiments, the amount of Na2CO3 in the raw material is adjusted between 0.005 and 0.015, and the performance of the doped ceramic sheets formed is similar, the piezoelectric constant is greater than 36pC / N, the best is 39.1 pC / N, and the Curie temperature is not less than 1190℃, indicating that it has good temperature stability. The relative density is greater than 99%, which can completely replace pure lithium niobate ceramics as high-temperature piezoelectric ceramics. Example 4
[0034] The other steps are the same as those in Example 1, and the process parameters are slightly adjusted. The difference is that step S8 adopts the conventional polarization process in the prior art. Example 5
[0035] The other steps are the same as those in Example 2, and the process parameters are slightly adjusted. The difference is that step S8 adopts the conventional polarization process in the prior art. Example 6
[0036] The other steps are the same as those in Example 3, and the process parameters are slightly adjusted. The difference is that step S8 adopts the conventional polarization process in the prior art.
[0037] The performance of the sliced Na-doped lithium niobate ceramic slices was tested, and the following table was obtained.
[0038] Piezoelectric constant Example 4 37.3 pC / N Example 5 37.6 pC / N Example 6 36.1pC / N The above table shows that in the three embodiments, the amount of Na2CO3 in the raw material is adjusted between 0.005 and 0.015, and the performance of the ceramic sheets formed is similar. However, a conventional polarization process is used. Compared with the polarization process of the present invention in Examples 1, 2, and 3, the piezoelectric constant is greater than 36pC / N, and the optimal value is 37.6pC / N. Although the piezoelectric performance is not significantly superior to that of Examples 1, 2, and 3, it is still significantly improved compared to the piezoelectric constant (25.2 pC / N) of pure lithium niobate ceramics in the original design. It can be seen that the polarization process of the present invention has a good optimization effect on the piezoelectric properties of the ceramic sheet, which is different from the original design process.
[0039] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of this patent.
Claims
1. A method for improving the piezoelectric properties of lithium niobate ceramics by Na doping, characterized in that The following steps are included: mixing S1: Li2CO3, Na2CO3, and Nb2O5 are weighed in a molar ratio of 0.985-0.995:0.005-0.015:1 to obtain a mixed powder, and then 5%-8% of anhydrous ethanol by weight of the mixed powder is added, and then ball milling is performed for 18-22 hours, and then taken out and dried in an oven to obtain a dry powder; Reaction S2: Place the above dried powder into a vacuum atmosphere furnace, evacuate the vacuum and raise the temperature to not less than 800°C, keep the temperature, and control the pressure in the furnace to 1.0-1.5×10 -3 Pa, the temperature is raised to not less than 950°C, and the temperature is kept for 2 to 4 hours. The reaction product is Na-doped lithium niobate powder; wherein the composition of the Na-doped lithium niobate powder is: Li 0.985~0.995 Na 0.005~0.015 NbO3; Hydrogen supply S3: After the insulation is completed, hydrogen is introduced into the vacuum atmosphere furnace to maintain the pressure in the pressure furnace at 1.0~1.2×10 5 Pa, keep the temperature in the furnace not less than 950°C, keep it warm for 5 to 6 hours, and obtain Na-doped lithium niobate powder rich in oxygen vacancy defects; wherein the composition of the Na-doped lithium niobate powder is: Li 0.985~0.995 Na 0.005~0.015 NbO 3~x , x is the number of oxygen vacancy defects in a single unit cell; Ball milling S4: ball milling the Na-doped lithium niobate powder to make its average particle size less than 3 μm; Sintering S5: The ball-milled Na-doped lithium niobate powder is sintered at high temperature. The sintering process conditions are: vacuuming the furnace until the pressure is no higher than 10 -3 Pa, the die stamping pressure is 50-80MPa, the heating rate is 80-100℃ / min, the temperature is raised from room temperature to not less than 950℃, kept at this temperature for 15-30min, cooled to not more than 600℃ at a rate of 15-25℃ / min, and then furnace cooled to obtain Na-doped lithium niobate ceramics; the composition of the Na-doped lithium niobate ceramics is: Li 0.985~0.995 Na 0.005~0.015 NbO 3~x ; Oxygenation S6; Slicing S7: cutting the above-mentioned Na-doped lithium niobate ceramic sheet without oxygen vacancy defects into blocks; Polarization S8: Place the above block into a high-voltage polarization device for polarization to obtain a polarized Na-doped lithium niobate ceramic sheet.
2. The method for improving the piezoelectric properties of lithium niobate ceramics by Na doping as claimed in claim 1, characterized in that The S5 oxygenation process is as follows: Na-doped lithium niobate ceramics are placed in an atmosphere heat treatment furnace, oxygen is introduced, and the pressure in the furnace is maintained at no less than 1.05×10 5 Pa, heating to not less than 850°C at a heating rate of 6-10°C / min, keeping the temperature for 25-30h, and then cooling to room temperature at a cooling rate of not more than 5°C / min to obtain Na-doped lithium niobate ceramics without oxygen vacancy defects.
3. The method for improving the piezoelectric properties of lithium niobate ceramics by Na doping as claimed in claim 1, characterized in that The S5 sintering process is: high temperature sintering using a spark plasma sintering furnace.
4. The method for improving the piezoelectric properties of lithium niobate ceramics by Na doping according to claim 1, characterized in that: In the mixing step S1, the molar ratio of Na2CO3, Li2CO3, and Nb2O5 is 0.015:0.985:0.985, and the composition of the prepared Na-doped lithium niobate ceramic is: Li 0.985 Na 0.015 NbO 3~x .
5. The method for improving the piezoelectric properties of lithium niobate ceramics by Na doping according to claim 1, characterized in that: In the mixing step S1, the molar ratio of Na2CO3, Li2CO3, and Nb2O5 is 0.005:0.995:0.995, and the composition of the prepared Na-doped lithium niobate ceramic is: Li 0.995 Na 0.005 NbO 3~x .
6. The method for improving the piezoelectric properties of lithium niobate ceramics by Na doping according to claim 1, characterized in that: In the mixing step S1, the molar ratio of Na2CO3, Li2CO3, and Nb2O5 is 0.01:0.99:0.99, and the composition of the prepared Na-doped lithium niobate ceramic is: Li 0.99 Na 0.01 NbO 3~x .
7. The method for improving the piezoelectric properties of lithium niobate ceramics by Na doping according to claim 1, characterized in that: In the polarization step, the polarization condition is to apply a high-voltage direct current electric field of not less than 15 kV / mm at both ends of the electrode, maintain it for 1.5 to 2 hours, and then cool it to room temperature to obtain the polarized Na-doped lithium niobate ceramic.
8. The method for improving the piezoelectric properties of lithium niobate ceramics by Na doping as claimed in claim 7, characterized in that: In the polarization step, before applying a high-voltage DC electric field at both ends of the electrode, the Na-doped lithium niobate ceramic sheet is placed in a high-voltage polarization device, immersed in methyl silicone oil, and slowly heated to 100°C.
9. A Na-doped lithium niobate ceramic prepared by any of the methods 1 to 8 above, characterized in that: The piezoelectric constant of the Na-doped lithium niobate ceramic sheet after polarization is 36.0~39.1 pC / N.
10. The Na-doped lithium niobate ceramic according to claim 9, characterized in that: The Curie temperature is not less than 1190°C, the relative density is not less than 99.3%, and the piezoelectric constant is 36.0-39.1pC / N.